Oxygen therapy limiting peripheral oxygen saturation to 89-93% is associated with a better survival prognosis for critically ill Covid-19 patients at high altitudes - Viruez Soto, Antonio (2022)
El Consejo Editorial es un equipo de expertos en el campo de la revista.